The Efficiency Analysis on Traditional Market in Salatiga, An Application of Data Envelopment Analysis - Lintangsari Susanto Putri; Evi Gravitiani (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
The traditional markets in Salatiga City are managed by the Unit Pelaksana Teknis Dinas (UPTD) Dinas Perdagangan. UPTD Dinas Perdagangan policy in Salatiga City is free rental fees for 3 years for newly built traditional markets. The objective of this study was to analyze the comparison of the level of efficiency of market management at the UPTD Dinas Perdagangan. The data used in this research are primary and secondary data obtained from the UPTD and Dinas Perdagangan Salatiga City. The method used in this study was a quantitative research method with the tools used is the Data Envelopment Analysis model of the Charnes, Cooper, dan Rhodes (CCR) dan Banker, Charnes, dan Cooper (BCC). The variable that is regulated in the research is the efficiency value of the UPTD Class A and B Dinas Perdagangan. The independent variables in the study included 2 variables, namely the input and output variables. Based on the analysis, the results of this study reveal that the two UPTDs have a balanced efficiency in their management and both UPTD Class A and Class B still make the development of traditional markets become in harmony with each other. In addition, market revitalization managed by UPTD for Class A and ClassB has been developing. The research suggestion is to maintain the results that have been achieved by the two UPTD Dinas Perdagangan. Both UPTDs have had innovations in managing traditional markets that have included the appropriate target market environment.